CEO OVERSEAS EXPERIENCE, CULTURAL DISTANCE AND CORPORATE FINANCIALIZATION: THE MEDIATING EFFECT OF ESG INVESTMENT IN CHINA (Journal of Technology and Operations Management, 2024)
Recently, Chief Executive Officers (CEOs) with overseas experiences show the “star effect”, according to upper echelons theory, CEOs’ overseas experiences might relate to corporate financialization, but there is little evidence of whether and how overseas CEOs affect it. Given the increasing trend of hiring overseas CEO in China, the study fills in the gap in the literature by examining the effect of CEOs with overseas experiences on corporate financialization. In sum, the study employs a two-way fixed effect model and SYS-GMM model to investigate the relationship between CEOs with overseas experiences and corporate financialization. Our findings still hold after the endogeneity disposal with a two-way fixed effect regression by lagging variables, Two-Stage Least Squares (2SLS), Heckman two-stageregression, and the propensity score matching (PSM). Moreover, the cultural distance between the host countries where CEO worked or received education and China inhibits corporate financialization, especially, Individualism vs Collectivism (IC) distance makes the most significant contribution. Furthermore, overseas CEOs primarily inhibit corporate financialization by improving ESG investment.